STUDIES OF NEAR-THRESHOLD AND LONG-RANGE AUTOIONIZATION SPECTRA OF RARE-EARTH ATOMS - Nafas Beknazarovich Eshqobilov; ?nvar Saparbayevich Kurbaniyazov (FAN, TA’LIM VA AMALIYOT INTEGRATSIYASI, 2020)
One of the brightest and most widely studied elements in this lantonoid group is the chemical element europium, which studies the Rydberg and autoionization states of rare-earth atoms. The atoms of europium (Eu) are in the group of 4f-electron atoms and belong to the group of lanthanides in the periodic table as a number of rare earth elements in terms of their physicochemical properties. The absorption spectra of atoms belonging to the lanthanide group have been partially studied and there are many reasons for this. The most important of these reasons is that absorption spectra have a complex structure. The absorption spectra of europium atoms are formed by superimposing the spectra of 6s2 electrons and spectra of 4f electrons.